PD-1 protein and gene expression as prognostic factors in early breast cancer. Issue 6 (10th November 2020) - Matikas, Alexios; Zerdes, Ioannis; Lövrot, John; Sifakis, Emmanouil; Richard, Francois; Sotiriou, Christos; Rassidakis, Georgios; Bergh, Jonas; Valachis, Antonis; Foukakis, Theodoros
Abstract : Background: There is a paucity of data on the prognostic value of programmed cell death protein 1 (PD-1) protein and gene expression in early breast cancer (BC) and the present study's aim was to comprehensively investigate it. Methods: The study consisted of three parts: a correlative analysis of PD-1 protein and gene expression from an original patient cohort of 564 patients with early BC; a systematic review and trial-level meta-analysis on the association between PD-1 protein expression and disease-free survival/overall survival (OS) in early BC; and a pooled gene expression analysis from publicly available transcriptomic datasets regarding PDCD1 expression. Results: In the study cohort, PD-1 protein, but not gene expression, was associated with improved OS (HRadj =0.73, 95% CI 0.55 to 0.97, p=0.027 and HRadj =0.88, 95% CI 0.68 to 1.13, p=0.312, respectively). In the trial-level meta-analysis, PD-1 protein expression was not found to be statistically significantly associated with outcomes in the overall population. Finally, in the pooled gene expression analysis, higher PDCD1 expression was associated with better OS in multivariable analysis in the entire population (HRadj =0.89, 95% CI 0.80 to 0.99, p=0.025) and in basal-like tumours. Conclusions: PD-1 protein and gene expression seem to be promising prognostic factors in early BC. Standardisation of detection and assessment methods is of utmost importance.